2010
DOI: 10.1038/onc.2010.11
|View full text |Cite
|
Sign up to set email alerts
|

Loss of poly(ADP-ribose) polymerase-2 leads to rapid development of spontaneous T-cell lymphomas in p53-deficient mice

Abstract: Poly(ADP-ribose) polymerase-2 (Parp-2) belongs to a family of enzymes that catalyse poly(ADP-ribosyl)ation of proteins. Parp-2 deficiency in mice (Parp-2) results in reduced thymic cellularity associated with increased apoptosis in thymocytes, defining Parp-2 as an important mediator of T-cell survival during thymopoiesis. To determine whether there is a link between Parp-2 and the p53 DNA-damage-dependent apoptotic response, we have generated Parp-2/p53-double-null mutant mice. We found that p53 À/À backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…Nicolás and co-workers have identified the accumulation of double strand breaks in PARP-2 -/-murine thymocytes [38]. This observation is in line with previous report by Yelamos and colleagues [24] who suggested that PARP-2 interacts with the Ku proteins, mediators of double strand break repair.…”
Section: Parp-2 In the Maintenance Of Genomic Integritysupporting
confidence: 82%
See 2 more Smart Citations
“…Nicolás and co-workers have identified the accumulation of double strand breaks in PARP-2 -/-murine thymocytes [38]. This observation is in line with previous report by Yelamos and colleagues [24] who suggested that PARP-2 interacts with the Ku proteins, mediators of double strand break repair.…”
Section: Parp-2 In the Maintenance Of Genomic Integritysupporting
confidence: 82%
“…Increased expression of a pro-apoptotic, bcl-2 homolog NOXA showed correlation with the enhanced apoptosis [47]. Apoptosis can be reversed by the removal of p53 [38] suggesting that cell death is induced by unresolved DNA damage. In line with this observation, when PARP-2 -/-mice were bred on a p53 -/-background, spontaneous lymphomas and to a smaller extent other sarcomas developed in the double knockout mice 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 [38] indicating a functional interplay between these two proteins in protecting genome integrity.…”
Section: The Role Of Parp-2 In Thymopoesis and Inflammatory Regulationmentioning
confidence: 91%
See 1 more Smart Citation
“…Although PARP-1 and PARP-2 have a wellestablished role in base excision repair of single-strand DNA breaks (6), these enzymes also participate in DSB repair (7)(8)(9). Poly(ADP-ribose) polymerase 1 contributes to DSB repair by regulating the stress-inducible transcription factor nuclear factor kB and is a key molecular driver in the DSB repair pathway backup NHEJ (B-NHEJ) (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…PARP-2 was abundantly expressed in the subcapsular zone of the thymus with decreased expression towards the center of the thymus suggestive of its involvement in thymocyte proliferation [11]. Indeed, PARP-2 deficient thymocytes die via p53-mediated apoptosis that leads to decreased number of CD4 + , CD8 + thymocytes in the thymus [12,13].…”
Section: Poly(adp-ribose) Polymerases In the Maturation And Differentmentioning
confidence: 99%